Hackathons as Affective Circuits: Technology, organizationality and affect. Issue 7 (July 2022) - Endrissat, Nada; Islam, Gazi
Technology invites a reconsideration of organization and organizing by calling attention to mediated forms of value production among loose social collectives outside formal organizational boundaries. While the nascent concept of organizationality holds potential for such a re-conceptualization, the processes through which loose social members become invested in co-orientation and collective effort require further empirical and theoretical exploration. In this paper, we link organizationality research with critical media studies on affect and technology to theorize how affect holds provisional collectives together while promoting new modes of value extraction. Empirically, we draw from an ethnographic study of hackathons – transdigital innovation spaces where participants act with and through technology – and suggest three intertwined processes as part of an affective circuit that stokes and directs affect. The paper's contribution is threefold. First, by analysing how affective circuits bind, integrate and co-orient action among loose members, we contribute to understanding organizationality as affectively constituted. Second, by showing how hackathons leverage desire for community, we offer a critical perspective on affective capture and argue that organizationality involves novel modes of value production. Third, we complement theorizing of hackathons by exploring them as sites of organizationality, focusing on the provisional, relational and affect-rich nature of new forms of organizing in the digital age.